Analisis Peran Influencer dan Brand Awareness terhadap Sales Pada Usaha Mikro Kecil Menengah - Busman, Aqilah Luthfiah; Muthmainna, Nafisah; Alimuddin, Firman (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2024)
The use of influencers marketing had become a popular strategy for UMKM to increase brand awareness and sales. This research aimed to analyze the role of influencers on brand awareness and sales in UMKM in Indonesia especially in Parepare UMKM namely Amaryllis Hijab. This research was qualitative research with the type of field research. The researcher used this research approach because of the problem that the researcher raised. The appropriate problem solving technique for finding answers to this research was to use a qualitative research approach, where data must be obtained through direct open interviews which were not enough if answered with just one question. This research was conducted in Parepare. Research subjects were objects, people, places, data for the object in question. In this case, the research was the Amaryllis Hijab shop in Parepare which has used the services of influencers to help increase brand awareness and product sales. Several related studies have found that influencers as business communicators via social media will significantly influence brand awareness and sales.